2022
DOI: 10.7150/thno.63481
|View full text |Cite
|
Sign up to set email alerts
|

An MMP-degradable and conductive hydrogel to stabilize HIF-1α for recovering cardiac functions

Abstract: Rationale: Although a few injectable hydrogels have shown a reliable biosafety and a moderate promise in treating myocardial infarction (MI), the updated hydrogel systems with an on-demand biodegradation and multi-biofunctions to deliver therapeutic drug would achieve more prominent efficacy in the future applications. In this report, a conductive and injectable hydrogel crosslinked by matrix metalloproteinase-sensitive peptides (MMP-SP) was rationally constructed to stabilize hypoxia-inducible fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…From the above data, we know that mature iPSC-CMs can generate more gap junctions than immature cells, and these results are also consistent with previous studies [ 57 ]. After MI, improving intercellular signaling and promoting the formation of new blood vessels are the two most important aspects of improving prognosis [ 58 ]. In the case of Gel loading, the generated gap junction results are better than the transplantation of pure mature iPSC-CMs.…”
Section: Resultsmentioning
confidence: 99%
“…From the above data, we know that mature iPSC-CMs can generate more gap junctions than immature cells, and these results are also consistent with previous studies [ 57 ]. After MI, improving intercellular signaling and promoting the formation of new blood vessels are the two most important aspects of improving prognosis [ 58 ]. In the case of Gel loading, the generated gap junction results are better than the transplantation of pure mature iPSC-CMs.…”
Section: Resultsmentioning
confidence: 99%
“…This success encouraged the development of a wide range of conductive hydrogel-based myocardial tissue engineering scaffolds. For example, Liu et al (2022) and Wei et al (2022) developed paintable and rapidly bondable conductive hydrogels as therapeutic cardiac patches, which can improve the reconstruction of cardiac function and revascularization of infarct myocardium ( Wei et al, 2022 ). Works by Qian et al (2018a) , Qian et al (2018b) , and Xu et al (2018) successfully demonstrated that nerve tissue engineering scaffold-coated graphene-loaded polycaprolactone based on a conductive hydrogel can transmit electrical signals, thus realising nerve tissue regeneration and functional reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…4 Cross-linked by MMP-sensitive peptides (MMP-SP), the multifunctional injectable hydrogel based on oxidized alginate (ALG-CHO) and HA was constructed to deliver 1,4dihydrophenonthrolin-4-on hydroxylase (PHD) and a stabilizer of HIF-1α for MI treatment. 125 3.11. Injectable Hydrogels for Minimally Invasive Delivery.…”
Section: Conductivitymentioning
confidence: 99%
“… Similarly, an ELRs-based hydrogel could allow for cell colonization and support post-MI remodeling . Cross-linked by MMP-sensitive peptides (MMP-SP), the multifunctional injectable hydrogel based on oxidized alginate (ALG-CHO) and HA was constructed to deliver 1,4-dihydrophenonthrolin-4-on hydroxylase (PHD) and a stabilizer of HIF-1α for MI treatment …”
Section: Hydrogels With Heart-specific Mimicry and Functionalitymentioning
confidence: 99%